Literacy Movement in Increasing Reading Interest of Elementary School Students - Azzahra, Annisa; Apoko, Tri Wintolo (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
The literacy movement and increasing interest in reading among students are essential educational challenges because literacy has a role in practice and social relations related to knowledge, Language, and culture. However, the problem of low literacy for Indonesian students still needs to be found. This study investigates the literacy movement in increasing the reading interest of students in elementary schools. The participants of this study are the students and the teachers at SDI PB Soedirman. The method used in this study is qualitative descriptive, namely, conducting direct observations and interviews with several selected students and teachers. The study results show that library visits, watching educational films, and holding literacy competitions have increased students' interest in reading, especially in grade IV. This activity can increase students' interest in reading and train students' courage in writing stories, speaking in public, or channelling their ideas. Thus, the literacy movement at SDI PB Soedirman should continuously be supported by adequate facilities and support from teachers so that the literacy movement can be channelled appropriately to students.